(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud storage enables users to remotely store their data and enjoy the on-demand high quality cloud applications without the burden of local hardware and software management. Though the benefits are clear, such a service is also relinquishing users’ physical possession of their outsourced data, which inevitably poses new security risks towards the correctness of the data in cloud. In order to address this new problem and further achieve a secure and dependable cloud storage service, we propose in this paper, a new cryptosystem for fine-grained sharing of encrypted data named Cipher text-Policy attribute-based encryption (CP-ABE). The cipher texts are labeled with sets of attributes and private keys are associated with access structures that control which cipher texts a user is able to decrypt. Attribute-based encryption (ABE) has been envisioned as a promising cryptographic primitive for realizing secure and flexible access control. The property based encryption extends the Attribute Set Based Encryption (ASBE) algorithm with a hierarchical structure to improve scalability and flexibility while at the same time it inherits the feature of fine-grained access control of ASBE. At the same time the data integrity of cloud storage is ensured by using (Message-Digest Algorithm) MD5 and Reed Solomon algorithm